Price response of the high fructose corn syrup industry in the United States: A Bertrand model application - Pablo A. Garcia-Fuentes; Philip Lynn Kennedy; Gustavo F. C. Ferreira (Journal of Applied Economics, 2022)
This paper uses a Bertrand duopoly model application and derives a high fructose corn syrup (HFCS) price reaction function that shows the response of the price of HFCS to changes in the price of sugar. It conducts cointegration analysis and assesses the performance of the HFCS price reaction model by estimating a Dynamic Ordinary Least-Squares model. It finds that the prices of HFCS-55, sugar, and corn are cointegrated over the period 1981:1 to 2017:12. The estimated long-run relationship shows that a one percent increase in the price of sugar increases the price of HFCS-55 by 0.19 percent. Additionally, the price of corn has a positive effect on the price of HFCS-55. The model and the results offer important insights for antitrust litigation.
Keywords: 330; Bertrand duopoly; high fructose corn syrup; price reaction; sugar; United States